Protecting People With Decisional Impairments and Legal Incapacity Against Biomedical Research Abuse - Noble, John H.; Sharav, Vera Hassner (Journal of disability policy studies, 2008)
Ethical and legal principles are provided for reviewing the ethics of recent cases of biomedical research abuse involving persons with decisional impairments or legal incapacity who were unable to understand the risks and benefits of the research to which they were subjected. Research abuse continues to occur despite guidance from the Nuremburg Code, the Declaration of Helsinki, the U.S. Belmont Report, extensive federal regulations governing human participant research, and several professional and disciplinary codes of ethics with which, the authors believe, the majority of researchers comply. Contributing to research abuse are weaknesses in the institutional review board and research ethics board review process; conflicting opinions about applicable ethical principles; mounting evidence of pervasive conflicts of interest; and dubious conflated research and marketing practices involving researchers, pharmaceutical and medical device manufacturers, and government research sponsors and regulatory agencies. Several recommendations are made to correct identifiable weaknesses and failures in the governance of biomedical research.